Analysis of CPU Usage Data Properties and their possible impact on Performance Monitoring - Stefanov, Konstantin S.; Gradskov, Alexey A. (Supercomputing Frontiers and Innovations, 2016)
CPU usage data (CPU user, system, iowait etc. load levels) are often the basic data used for performance monitoring. The source of these data is the operating system. In this paper we analyze some properties of CPU usage data provided by Linux kernel. We examine kernel source code and provide test results to find which level of accuracy and precision one may expect when using CPU load level data.